2010
DOI: 10.1590/s1983-14472010000300025
|View full text |Cite
|
Sign up to set email alerts
|

Nine Equivalents of Nursing Manpower Use Score (NEMS): um estudo de seu processo histórico

Abstract: This study aims to describe, through an integrative review of literature, the historical trajectory of therapeutic intervention scores with emphasis on Nine Equivalents of Nursing Manpower Use Score in Intensive Care Units. The descriptors "Intensive care units" and "scales" were looked up in publications issued between 2000 and 2009. The terms selected were: "Nine Equivalents of Nursing Manpower Use Score" or "NEMS", "Unidade de Terapia Intensiva", "Therapeutic Intervention Scoring System-76", "Therapeutic In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 14 publications
2
11
0
1
Order By: Relevance
“…The main advantages of using NEMS are the reduction in data collection time and the ease with which this score can be applied . Limitations were also observed in studies, where it was found that NEMS has less discriminative power when compared with TISS‐28: patients with the same score do not always require the same care; patient age can influence the score value; it does not include nursing activities not related to patient care …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main advantages of using NEMS are the reduction in data collection time and the ease with which this score can be applied . Limitations were also observed in studies, where it was found that NEMS has less discriminative power when compared with TISS‐28: patients with the same score do not always require the same care; patient age can influence the score value; it does not include nursing activities not related to patient care …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Limitations were also observed in studies, where it was found that NEMS has less discriminative power when compared with TISS-28: patients with the same score do not always require the same care; patient age can influence the score value; it does not include nursing activities not related to patient care. 7 Research with nursing indicators is still ongoing in Brazil. However, the Brazilian Health Surveillance Agency (ANVISA) published Board Resolutions, RDC No.7 in 2010 and RDC no.…”
Section: Introductionmentioning
confidence: 99%
“…Some changes were implemented to it over time and its simplified version is currently the most disseminated of its versions. (1,2) The Therapeutic Intervention Scoring System-28 (TISS-28), presented in 1996, is composed of 28 items designed to measure the severity of the disease and nursing workload. (2,3) The creation of the Nine Equivalents of Nursing Use Manpower (NEMS) (2,4) was based on the TISS-28.…”
Section: Introductionmentioning
confidence: 99%
“…(1,5,6) The NEMS is also appropriate for the management of nursing professionals who work in intensive therapy and for the evaluation of ICUs. (7)(8)(9) Studies validating NEMS were implemented with clinical and surgical patients hospitalized in adult ICUs, (4,10) however, such studies are rare and seldom implemented in pediatric units.…”
Section: Introductionmentioning
confidence: 99%
“…It includes 28 items that cover seven major categories: basic activities, ventilatory support, cardiovascular support, renal support, neurological support, metabolic support, and specific interventions. ( 7 ) The NEMS, which is simpler and more objective, ( 4 , 8 , 10 , 11 includes nine items from the TISS-28: basic monitoring, intravenous medication, mechanical ventilatory support, supplementary ventilatory care, single vasoactive medication, multiple vasoactive medication, dialysis techniques, specific interventions in the ICU and specific intervention outside the ICU. ( 8 ) In practical terms, to produce reliable measurements, nursing personnel using these scales must be knowledgeable about how to interpret each item.…”
Section: Introductionmentioning
confidence: 99%